The Utilization Of Drill And Practice Youtube Video Model To Improve English Proficiency In Elementary Schools - Muhammad Najib; Maya Rahma Sarita; Ani Khoirotun Nisa; Andi Prastowo (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2023)
English as a local content in elementary schools, but students lack the desire and enthusiasm to learn English, students think that English is very difficult both pronunciation and writing. The purpose of the study is to utilize YouTube videos as learning media using the Drill and Practice method to improve English vocabulary in elementary schools, this study uses a Classroom Action Research (PTK) approach, the results of the study that the utilization of YouTube videos using the Drill and Practice model can improve English language skills in fourth grade students of SD Negeri 4 Metro Barat, with research subjects 20 students produced good results and experienced an increase in learning outcomes. In the pre-cycle the level of completeness of student learning outcomes was 40%, in cycle I the level of completeness of learning outcomes was 60%, in cycle II it increased with a level of completeness of learning outcomes of 95%, so the level of completeness of student learning outcomes in cycles I and II increased by 30%. So it can be concluded that by utilizing YouTube videos using the Drill and Practice method can improve English language skills in elementary schools.